Analisis Efisiensi Dan Keberlanjutan Ekonomi Syariah Dalam Konteks Pemilu 2024 di Indonesia: Bibliography Study - Imanestia Habibah, Inna; Sita Maulida, Dewi (Prodi Ekonomi Syariah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2023)
This research aims to investigate the impact of the 2024 General Election on Islamic economy in Indonesia using an integrated approach. The primary focus of this study is to develop an analytical model that encompasses economic efficiency, market sentiment, and relevant government policies. By employing sentiment analysis in the market and Islamic investment, the research intends to depict the relationship between public political choices and their effects on market confidence and investment decisions in the Islamic financial sector. Additionally, the study will assess the current government policies' impact on the growth of the Islamic economy and formulate improvement recommendations to support the stability of this sector. Through case studies on Islamic banks undergoing significant changes post-election, the research will deepen the understanding of adaptive operational strategies and their impact on the stability and efficiency of the Islamic financial sector. The results of this research are expected to provide a holistic view of the interconnection between political dynamics, the Islamic economy, and government policies, laying the foundation for the development of sustainable Islamic economic strategies in Indonesia.